AKTIVITAS BAKTERISIDA EKSTRAK CEM-CEM (Spondias pinnata (l .f) Kurz) TERHADAP BAKTERI Erwinia chrysanthemi PENYEBAB PENYAKIT BUSUK LUNAK LIDAH BUAYA - Ni Komang Ariati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2012)
A compound with antibacterial activity has been isolated from cem-cem (spondias pinnata (L.f) kurz). Antibacterial activity test towards Erwinia chrysanthemy resulted in VIII fraction. Fraction V effectively inhibited the growth of Erwinia chrysanthemy. The analysis of the active fraction with GC-MS (Gas Chromatography-Mas Spectrophotometer) showed that the active fraction contains Methyl Ester.